Konsep Ṭayyib dalam Al-Qur’an: Perspektif Tafsir Ilmi terhadap Keamanan Pangan, Nilai Gizi, dan Kesehatan Preventif - Indita Rinanty Br Damanik; Abdul Halim; Husna Sari (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2026)
The increasing challenges of food safety due to biological and chemical contamination, the decline in the nutritional quality of modern consumer products, and the high prevalence of diet-related non-communicable diseases indicate the need to strengthen the food paradigm that is oriented not only to legal aspects but also to health. In this context, studies on food in Islam are still dominated by discussions of halal. At the same time, the dimension of ṭayyib has not received adequate attention as a concept related to consumption quality and health protection. This study aims to analyze the concept of ṭayyib in the Qur’an through the perspective of scientific interpretation and examine its relevance to food safety, nutritional value, and preventive health. The method used is a qualitative research study based on a literature review, with a mawḍūʻī interpretation approach to verses containing the term ṭayyib, supported by analysis of classical, modern, and contemporary interpretation literature and by dialogue with findings from food, nutrition, and health sciences. The study results show that the concept of ṭayyib encompasses a range of meanings that extend beyond formal halal certification, emphasizing safety from harmful elements, adequate and balanced nutritional content, food quality, and an orientation toward preventing health risks. This concept forms a consumption paradigm that prioritizes human biological well-being by selecting foods that are safe, nutritious, and support the maintenance of bodily functions. The analysis also demonstrates substantial alignment between the concept of ṭayyib and modern scientific principles regarding food safety, nutritional adequacy, and preventive medicine. These findings confirm that the concept of ṭayyib can be positioned as a normative and scientific framework that bridges Qur’anic studies with contemporary health sciences.